2019
DOI: 10.3390/nu11081860
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lactase Persistence Genotypes (rs4988235) and Ethnicity with Dairy Intake in a Healthy U.S. Population

Abstract: Lactase persistence (LP) is a trait in which lactose can be digested throughout adulthood, while lactase non-persistence (LNP) can cause lactose intolerance and influence dairy consumption. One single nucleotide polymorphism (SNP ID: rs4988235) is often used as a predictor for dairy intake, since it is responsible for LP in people in European descent, and can occur in other ethnic groups. The objective of this study was to determine whether rs4988235 genotypes and ethnicity influence reported dairy consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
(87 reference statements)
0
17
1
Order By: Relevance
“…Lactose was estimated by manually looking up ASA24-reported foods into Nutrition Data System for Research (NDSR). The servings of total dairy are from the standard ASA24 output, with servings of soymilk subtracted [10,11]. The blue dashed line indicates the linear line of best fit.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Lactose was estimated by manually looking up ASA24-reported foods into Nutrition Data System for Research (NDSR). The servings of total dairy are from the standard ASA24 output, with servings of soymilk subtracted [10,11]. The blue dashed line indicates the linear line of best fit.…”
Section: Figurementioning
confidence: 99%
“…We use lactose as a case study and estimate values from foods recorded from ASA24 recalls by a California cohort of healthy adults [25]. To address the first scenario, we trained and tested nine machine learning models on the ability to predict the amount of lactose in a given ASA24 food, Nutrients 2019, 11,3045 4 of 27 comparing the predicted lactose values to the lactose obtained by manually looking up ASA24 foods into NDSR. For the second scenario, we developed a database matching algorithm that used only the 62 nutrients shared between the ASA24 output and the NCC database to return the best NCC food match for a given ASA24 food, as well as another algorithm that used both the nutrients and text descriptions of the foods.…”
Section: Figurementioning
confidence: 99%
“…Some studies have found that milk or total dairy consumption is associated with the LP genotype [43][44][45][46][47]. Other studies have shown that LP genetics has no influence over whether a participant is a cow milk consumer [48][49][50]. Most of those studies were conducted in populations with high frequencies of the LP phenotype and high amounts of milk consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Asians are known to have higher prevalence of intolerance than other ethnicities. It has been reported that in all ethnic populations and especially among Caucasians, LP individuals tend to consume more cheese and recent total dairy intake (35). In LP, lactose is broken down by the enzyme lactase in the small intestine, resulting in the formation of D-galactose, which has been extensively shown to induce neurodegeneration through oxidative stress in animal models.…”
Section: Discussionmentioning
confidence: 99%